Analysis of the Correlation Between Healthy Lifestyle Patterns and Work Stress in Psychiatric Nurses (International Journal of Studies in Nursing, 2022)
Introduction: This study explores the status of mental healthcare workers in the eastern region with respect to work pressure, health-promoting lifestyle patterns, and their related factors, which can provide an important reference to aid the formulation and development of health promotion strategies for such individuals. Methods: A total of 115 questionnaires were distributed and 112 valid questionnaires were recovered, with a recovery rate of